2015
DOI: 10.1016/j.btre.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on ideal mode of cell disruption in extremely halophilic Actinopolyspora halophila (MTCC 263) for efficient release of glycine betaine and trehalose

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
(61 reference statements)
0
9
0
2
Order By: Relevance
“…El Zakhem et al (2006) observed release of ionic substances, peptides and proteins by PEF treatment of Saccharomyces cerevisiae at 5 kV/cm. A recent work showed that the osmotic pressure 1.9 kPa was enough to break the microbial cells (Kar, & Singhal, 2015). Non-mechanical method consumed modest or low energy followed by high selective product recovery, thus preferred as mild disruption methods.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…El Zakhem et al (2006) observed release of ionic substances, peptides and proteins by PEF treatment of Saccharomyces cerevisiae at 5 kV/cm. A recent work showed that the osmotic pressure 1.9 kPa was enough to break the microbial cells (Kar, & Singhal, 2015). Non-mechanical method consumed modest or low energy followed by high selective product recovery, thus preferred as mild disruption methods.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The cryoprotectant activities of trehalose and GB is consistent with their known roles in the microbial cells. [4,11] The mechanism by which GB provides cryoprotection is not yet understood. In tomatoes, exogenous application of GB is reported to improve its chilling tolerance which may be due to higher catalase activity in GB treated tomato plants [5] that over express the catalase gene (CAT1).…”
Section: Microscopic Analysis Of Peas After 90 Day Storagementioning
confidence: 99%
“…GB is utilized by the food, agricultural, pharmaceutical, and other industries for a variety of applications. [11] Biogenic GB is commercially produced from beet molasses and marine alga Ascophyllum nodosum. [12,13] Acid whey, a waste material of the dairy industry, can also be fermented to produce GB.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for preferring mechanical methods to chemical and enzymatic methods for cell disruption on the industrial scale is to avoid the increase in unit operation steps during downstream processing. 12 Bead mills represents the most effective ways for mechanical disruption of microbial cells with high disruption efficiency, good temperature control and easy scaleup procedure. High-pressure homogenizers are most commonly used for bacteria and yeast disruption in the pharmaceutical and biotechnological industries.…”
Section: Introductionmentioning
confidence: 99%